Mimicry and Resistance in Pramoedya Ananta Toer’s Bumi Manusia: A Postcolonial Reading through Homi K. Bhabha’s Theory - Nensilianti, Nensilianti; Ridwan, Ridwan; Sakti M, Reztu Dwi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines the dynamics of mimicry and indigenous resistance portrayed in Bumi Manusia (This Earth of Mankind) by Pramoedya Ananta Toer through a postcolonial perspective. Grounded in Homi K. Bhabha’s theory of mimicry, the research investigates how colonial subjugation shaped the emergence of cultural resistance among indigenous characters. Employing a qualitative textual analysis with a dialectical approach, the study proceeds through three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that mimicry operates as an ambivalent cultural strategy—simultaneously reproducing and undermining colonial authority. Four distinct forms of resistance emerge as the characters negotiate identity, agency, and autonomy under colonial domination. These forms demonstrate that mimicry functions not merely as imitation but as a subversive act of decolonial affirmation and identity reconstruction. The study contributes to postcolonial literary scholarship by situating Bumi Manusia within the broader discourse of decolonization and cultural hybridity in Southeast Asian literature. It also offers a localized understanding of subaltern resistance that enriches global discussions on the intersections of power, culture, and postcolonial subjectivity.